DNA polymerase II is encoded by the DNA damage-inducible dinA gene of Escherichia coli. - C A Bonner; Sharon L. Hays; Kathleen Mc Entee; Myron F. Goodman (1990)
The structural gene for DNA polymerase II was cloned by using a synthetic inosine-containing oligonucleotide probe corresponding to 11 amino acids, which were determined by sequencing the amino terminus of the purified protein. The labeled oligonucleotide hybridized specifically to the lambda clone 7H9 from the Kohara collection as well as to plasmid pGW511 containing the SOS-regulated dinA gene. Approximately 1400 base pairs of dinA sequence were determined. The predicted amino-terminal sequence of dinA demonstrated that this gene encoded DNA polymerase II. Sequence analysis of the upstream region localized a LexA binding site overlapping the -35 region of the dinA promoter, and this promoter element was found to be only two nucleotides downstream from the 3' end of the araD gene. These results demonstrate that the gene order is thr-dinA (pol II)-ara-leu on the Escherichia coli chromosome and that the DNA polymerase II structural gene is transcribed in the same direction as the araBAD operon. Based on the analysis of the predicted protein, we have identified a sequence motif Asp-Xaa-Xaa-Ser-Leu-Tyr-Pro-Ser in DNA polymerase II that is highly conserved among a diverse group of DNA polymerases, which include those from humans, yeast, Herpes and vaccinia viruses, and phages T4 and PRD1. The demonstration that DNA polymerase II is a component of the SOS response in E. coli suggests that it plays an important role in DNA repair and/or mutagenesis.